Controle de Tráfego Aéreo Autônomo: Simulação de Sistemas Multiagentes com o framework JaCaMo na plataforma Unity - Viero, Bernardo; Bordini, Rafael H.; Zamberlan, Alexandre (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2024: Anais do XVIII Workshop-Escola de Sistemas de Agentes, seus Ambientes e AplicaçõesDO - 10.5753/wesaac.2024.33461, 2024)
This research aims to unite the areas of Multi-Agent Systems (MAS) and Simulation in the management and control of autonomous air traffic. The simulated agents represent aircraft, control towers, and runways for landing and takeoff, with the ability to perceive, plan, execute, and communicate with each other. The behavior of the agents should be emergent and dynamic, meaning that the simulations should generate states or situations requiring the agents to plan, communicate, and negotiate. For this, the Java and AgentSpeak(L) languages, and the Jason interpreter are used for server construction, while the C# language and the Unity platform are used for the implementation of the simulations.